PENGARUH KUALITAS PELAYANAN MARKETING SPEKTRA MULTI FINANCING TERHADAP KEPUASAN KONSUMEN PADA PERUSAHAAN SPEKTRA MULTI FINANCING DISAMARINDA - -, Muhamad Zaenudin (EKONOMIA, 2014)
Objectives and expected usefulness of this study was to determine the effect of service quality in the form of (reliability, responsivensess, asspengaruhurance, empathy, and tangible) significant influence on consumer satisfaction in the company spectra Mualti Financing in Samarinda and knowing of the variable quality of service (reliability, responsivensess, asspengaruhurance , empathy, and tangible) where the dominant influence on customer satisfaction in the company spectra Multi Financing in Samarinda. The results of the analysis based on data from the population and the sample of 30 respondents and data management questionnaire, the study produced the following regression equation: Y = -8.447 + 0.627 + X1 + 0,500X2 0,092X3 + 0,180X4 + 0,297X5. the results of these equations can be known constants (Î±) of -8.447 states that if X1, X2, X3, X4, and X5, equal to zero then the level of customer satisfaction will decrease by -8.447 or can be said if there is no variable reliability, responsiveness, assurance , empathy and tangible hence customer satisfaction will be decreased by -8.447. The F-test results can count equal to 8.627 M, while the value of F table at 3.40 this means that in the entire (Fhitung 8627> Ftable 3.40) so that it can be said variable reliability, responsiveness, assurance, empathy and tangible jointly able to demonstrate influence on customer satisfaction. Figures R is 0.802 matter is that the correlation between the variable reliability, responsivensess, asspengaruhurance, empathy, and tangible to customer satisfaction is very strong hubunganya. Angaka adjusted R is 0.643 or 64.3% customer satisfaction rate is influenced by the variable reliability, responsivensess, asspengaruhurance, empathy, and tangible while the remaining 35.7% influenced by factors that are not included in this study. Based on the t test and correlation tables, looks variable reliability of the most dominant influence of 0.372 or 37.2% of consumer satisfaction, followed by variable responsivness of 0,303, or 30.3%, tangible variable of 0.295 or 29.5%, the variable empathy of 0.143 or 14.3% and variable assurance of 0.070 or 7.0%